Enantiomeric separation and quantitation of warfarin and its metabolites in human plasma by LC-MS/MS - Mostafa, Ahmed Abd-Alazim (European Journal of Chemistry, 2016)
The enantiomeric separation of warfarin (WAR) enantiomers and its hydroxy metabolites positional isomers is described in this work. The utilization of chiral chromatography coupled to Tandem mass spectrometry helps to achieve that. The developed method was able to separate R,S-warfarin and enantiomers of 4,7,10-hydroxy warfarin in human plasma. Plasma samples were processed with simple protein precipitation with acetonitrile. The chromatographic separation was done on chiral Astec Chirobiotic V column with gradient flow of 0.1% aqueous formic acid and 0.1% formic in acetonitrile:water (95:5, v:v). The mass spectroscopic detection was done via negative mode multiple reaction monitoring (MRM) on a triple quadrupole mass spectrometer coupled with positive electrospray ionization (ESI). Linearity of the method was valid over a concentration range of 125.00-0.13 µg/mL for racemic WAR, 47.000-0.088 µg/mL for racemic 4’-OH-WAR, 56.00-0.18 µg/mL for racemic 7-OH-WAR and 56.00-0.02 µg/mL for racemic 10-OH-WAR. The LLOQs were found to be 0.13 µg/mL for racemic WAR, 0.088 µg/mL for racemic 4’-OH-WAR, 0.18 µg/mL for racemic 7-OH-WAR and 0.02 µg/mL for racemic 10-OH-WAR. The method was validated for matrix effect, intra- and inter-day precision, freeze/thaw and storage stability. Accuracy and precision were within acceptable range (<15%). Enantiomeric forms of WAR and its metabolites were separated by the chiral column. Standards for R- and S-WAR identified peak 2 as S-WAR while metabolite peaks could not be definitively identified. Peak 2 for 7-OH-WAR gave higher blood levels, while the opposite applied to 10-OH-WAR.